STRATEGIC MANAGEMENT ANALYSIS OF PT. CITRA PERDANA KENDEDES MALANG IN FACING THE RISE OF ONLINE TRANSPORTATION (A Case Study) - CAHYANTI, ADHELIA REGITA (Jurnal Ilmiah Mahasiswa FEB, 2020)
Along with the development of technology, conventional taxi companies began to be threatened, since it can be ordered through an application on smartphone. It is known as online transportation. The purpose of this research is to explain the strategy formulation of PT. Citra Perdana Kendedes based on their vision, mission, goals, and the application of internal and external environment analysis. This research used a case study qualitative method. The research was conducted by analyzing the company's internal and external environment, which was then incorporated into the SWOT Matrix (Strength, Weakness, Opportunity, Threat), Grand Strategy Matrix, and SPACE Matrix (Strategic Position and Action Evaluation) in formulating the company strategies. To collect data, this research used interview techniques, documentation, observation, and literature study. From the analysis, this research suggests that PT. Citra Perdana Kendedes needs to conduct a market development strategy, product development, and market penetration to be able to competewith other participants.Keywords: Strategic Management, Conventional Taxi, SWOT Matrix, GrandStrategy Matrix, SPACE Matrix.